Marburg Virus Disease: A Narrative Review - Arash Letafati; Somayeh Sadat Hosseini Fakhr; Ali Qaraee Najafabadi; Negin Karami; Hassan Karami (Health Science Reports)
ABSTRACT Background and Aims Given the recent deadly outbreaks of the Marburg virus (MARV), in early 2023 in Tanzania and Equatorial Guinea, and the most recent one in Rwanda in 2024, there has been renewed attention across Africa on the threat posed by the re‐emergence of MARV as a growing concern for public health. Therefore, it needs to provide a comprehensive overview of the virus and its related infections, encompassing virus classification, historical outbreaks, transmission dynamics, the intricate interface between the virus and its hosts, the methods of diagnosis, core prevention strategies, and current therapeutic options, to better understand the virus and the disease characteristics in responding to future outbreaks. Methods For this review, four scientific online databases, including PubMed, Google Scholar, Scopus, and Web of Science were thoroughly searched for peer‐reviewed journal papers (original, case reports/series, and review studies) published in English language using the following keywords: Filovirus, Marburg virus, Marburg Haemorrhagic Fever, Marburg virus disease, and Marburg virus outbreak. Results MARV shares similarities with its close cousin —the Ebola virus [EBOV]—in terms of viral characteristics and most clinical features. These two viruses are of animal origin and primarily spread to humans through infected bats (both direct and indirect close contact), which serve as the common natural host reservoirs. The potential for interhuman transmission, coupled with the ability to cross borders of endemic regions combined with the absence of a licensed vaccine and effective treatment, have made MARV a significant threat to human health. This virus is clinically characterized by a range of symptoms and organ dysfunctions. The disease is often fatal in a significant proportion of infected individuals. This viral infection is diagnosed by various diagnostic tools, prevented mainly through personal protective measures, and treated usually with clinical management and supportive care. Conclusion The outbreaks of MARV are continuously threaten public health; therefore, the world must be alert and well‐prepared. For MVD, taking precautions along with investing in research and preparedness at regional, national, and global levels is of crucial importance and should be prioritized.